Feminism's progress : gender politics in British and American literature and television since 1830 - Colatrella, Carol (SUNY series in feminist criticism and theory., 2023)
"Explores how popular novels, short stories, and television shows from the United States and Britain illustrate the positive effects of feminism and promote gender equity"--